Evolução de uma Ferramenta de Gerenciamento de Configuração de Software através da Engenharia Reversa - Beraldi, Lairce Castanhera; Sanches, Rosely; Yamashiro, Fátima (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1997)
The items that comprise all information produced as parts of the software engineering process are collectively called Software Configuration, and constitute an important resource to the professional that works with software since it should be complete an up-to-date. The existence of an appropriate software configuration that reflects to reality depends on an effective Software Configuration Magement process. The activities involved in the software configuration management process are complex and the necessity of tools to support them comes into view. Usually these tools are too expensive and not available to every one that needs them. The Reviston Control System (RCS), in spite of not being a tool for software configuration management, because it supports only a few activities related with the management process, can be of great help to case this task. Furthermore, RCS is a public domain system. Only difficulty using RCS is related to its interface: usually based on command lines. This work aims at providing a graphic interface to RCS so that this system would be more user friendly. To achieve this, firstly the RCS code was submitted to a process of reverse engincering, using the FUSION-RE method. This method produces object-oriented analysis models (FUSION's models) from procedural code systems. The reverse engineering process provided a more abstract view of the system that was considered in the development of the graphic interface using Xview.